Gastrointestinal adverse reactions reduce the success rate of Helicobacter pylori eradication therapy: A multicenter prospective cohort study. Issue 2 (23rd December 2020) - Kakiuchi, Toshihiko; Matsuo, Muneaki; Endo, Hiroyoshi; Sakata, Yasuhisa; Esaki, Motohiro; Noda, Takahiro; Imamura, Ichiro; Hashiguchi, Kazutoshi; Ogata, Shinichi; Fujioka, Yasuhiko; Hanada, Keiichiro; Fukuda, Kayoko; et al.
Abstract: Background: The screening and treatment of Helicobacter pylori infection for all junior high students in Saga Prefecture, Japan, were started in 2016. The present study aims to evaluate the influence of adverse reactions on the success of the eradication therapy. Methods: From 2017 to 2019, 25, 006 third‐grade junior high school students were tested for urinary anti‐ H. pylori antibodies. Positive cases were confirmed by H. pylori stool antigen tests. Of the 531 students who were found to be H. pylori ‐positive, 390 (358 in first‐line and 32 in second‐line therapy) underwent eradication therapy, and 274 (242 in first‐line and 32 in second‐line) students actually completed a self‐reported form to rate stool consistency (based on the Bristol Stool Scale), the maximum number of bowel movements, and abdominal symptoms during the 7 days of treatment. Results: Among the 274 students, the total of primary and secondary eradication success rates was 87% (95% confidential interval: 82.9–90.1) in intention‐to‐treat analysis. On days 4, 5, and 6, stool consistency was looser in the primary eradication failure group than in the success group ( p  < .05). Looser stool consistencies were observed in male students with abdominal pain compared to those who did not experience pain ( p  < .05). Abdominal pain and diarrhea were detected in 28.5% and 42.7% of the subjects, respectively. The overall incidence of other adverse events was low ( n  = 8/274, 2.9%), and only two students discontinued treatment because of adverse events. Conclusions: Softening of the stool was related to the eradication failure in the junior high school students, especially in males with abdominal pain. Adverse effects did not induce discontinuation of the eradication treatment.